Pengaruh dari Konsentrasi Elektrolit Tembaga Asetat-Asam Asetat dan Temperatur terhadap Efisiensi Arus pada Elektrodeposisi Baja Karbon Rendah dengan Tembaga: Effect of Electrolyte Concentration of Copper Acetic-Acetic Acid and Temperature on Current Efficiency in Electrodeposition of Low Carbon Steel with Copper - Widya Yeni Rawati; Warsono; Sri Widarti (KOVALEN: Jurnal Riset Kimia, 2022)
One example of an electrolysis practicum module at the Chemistry Laboratory is the plating of copper on low-carbon steel metal with cyanide as the electrolyte. This cyanide electrolyte is commonly known as Zonax Copper. Due to the dangerous cyanide content, a replacement electrolyte that is safe, cheap, and easy to obtain for student practicum scales is sought. The purpose of this study was to determine the optimum temperature and composition of copper acetate-acetic acid as indicated by the largest current efficiency value. The composition of Cu-Acetate/Acetic Acid varied 0.2/0.4; 0.4/0.6; 0.6/1.2; 0.8/1.6, and 1/2 gram/250 mL. The coating process was carried out at temperatures of 30, 40, 45, 50, and 60oC with an electrodeposition time of 10 minutes. The results show that the highest current efficiency was found in the composition (CH3COO)2Cu/CH3COOH 1gram/ 2 ml, temperature 45℃ by 93%. The effect of temperature on current efficiency is in the form of a second-order polynomial with a correlation of research results >90%. The average maximum temperature is 42.68oC and the largest current efficiency is 96% at a concentration of (CH3COO)2Cu/CH3COOH 0.6 gr/1.2 ml. The current efficiency is directly proportional to the logarithmic concentration at temperatures of 30, 40, 45, and 50oC.